Preoperative Antibiotics for Septic Arthritis in Children: Delay in Diagnosis. (April 2015) - MacLean, Simon BM; Timmis, Christopher; Evans, Scott; Lawniczak, Dominik; Nijran, Amit; Bache, Edward
Purpose: To review the records of 50 children who underwent open joint washout for septic arthritis with (n=25) or without (n=25) preoperative antibiotics. Methods: Records of 50 children who underwent open joint washout for presumed septic arthritis with (n=25) or without (n=25) preoperative antibiotics were reviewed. 17 boys and 8 girls aged 3 weeks to 16 years (median, 1.5 years) who were prescribed preoperative antibiotics before joint washout were compared with 12 boys and 13 girls aged one month to 14 years (median, 2 years) who were not. Following arthrotomy and washout, all patients were commenced on high-dose intravenous antibiotics. Patients were followed up for 6 to 18 months until asymptomatic. Results: Patients who were referred from places other than our emergency department were twice as likely to have been prescribed preoperative antibiotics (p=0.0032). Patients prescribed preoperative antibiotics had a longer median (range) time from symptom onset to joint washout (8 [2–23] vs. 4 [1–29] days, p=0.05) and a higher mean erythrocyte sedimentation rate (93.1 vs. 54.3 mm/h, p=0.023) at presentation. Nonetheless, the 2 groups were comparable for weight bearing status, fever, and positive culture, as well as the mean (range) duration of antibiotic treatment (4.9 [4–7] vs. 4.7 [1–8] weeks, p=0.586). Conclusion: Preoperative antibiotics should be avoided in the management of septic arthritis in children. Their prescription delays diagnosis and definitive surgery, and leads to additional washouts and complications. A high index of suspicion and expedite referral to a specialist paediatric orthopaedic unit is needed if septic arthritis is suspected.